Thematic analysis of scientific publications dedicated to the development of a greeting card in the context of its historical and socio-cultural - Davydova, Kateryna Oleksandrivna (Theory and practice of design, 2022)
The purpose. To carry out a thematic review of scientific works published in recent years and devoted to the emergence and historical development of the postcard greeting card of the late nineteenth — early twentieth century in the context of its historical and socio-cultural development. The research methodology. The article uses well-known art methods: historical-cultural, historical-attribute, which cover the process of formation of a greeting card from the standpoint of socio-cultural and historical heritage, and not only from the standpoint of information, contribute to the evolution and figurative transformation of the greeting card. chronological order. Along with this, general scientific methods are used: comparative, analysis, synthesis, monitoring, systematization, statistical, historical and chronological, which allows scientists to analyze the communicative, philological component, to reveal the collection and classification of postcards. Based on this, we gain additional knowledge about the object of study. The results. A thematic review of scientific works published in recent years and devoted to the emergence and historical development of the postal greeting card of the end of the 19th — beginning of the 20th century in the context of its historical and socio-cultural development was conducted. The problems, content and main ideas of scientific publications are considered, in which scientists conduct an analysis of the communicative and philological component, reveal the issue of collecting and classifying postcards, highlight the process of creating a postal greeting card from the standpoint of socio-cultural and historical heritage, and not only from the standpoint of a means of transmission information. An overview of the directions of scientific research on postcards of the end of the 19th and the beginning of the 20th centuries was carried out. The authors of scientific works, for the most part, consider the history of the origin and formation of the greeting card (historical component), consider the postcard as one of the currents of fine art, in the context of studying the socio-cultural development of the corresponding historical period of time, propose methods of classification and attribution of postcards, considering the postcard from the point of view collecting, offering their approaches to exhibiting collectible collections of postcards by thematic areas. The article also includes scientific publications by authors who researched not only the front side of the postcard, which contains an artistic (graphic) image, but also the reverse side, which contains the text, postmarks, country of origin, dates of dispatch (production), etc. Attention is focused on the work, where the author for the first time carried out an analysis of the main directions of using the texts of open letters and developed methodical recommendations for their study. As a result of research, it was established that the majority of modern scientific works, articles and other publications on a certain topic belong to Russian scientists. The Ukrainian greeting card as an object of study of the phenomenon of graphic art remains out of the attention of domestic researchers, especially in the context of design. This requires further art studies of the peculiarities of the design of the domestic postal greeting card of the end of the 19th and the beginning of the 20th centuries from the standpoint of figurative, stylistic and cultural potential. Scientific novelty. Is to consider the issues, content and main ideas of scientific publications, in which scientists analyze the communicative, philological component, reveal the collection and classification of postcards, highlight the process of creating a greeting card from the standpoint of socio-cultural and historical heritage, not just means of transmitting information. Practical significance. Dissertation research can serve as a basis for practical work with postcard funds in departments of libraries, archives and museums; for the development of methodological recommendations aimed at improving the modern practice of publishing art postcards; while reading courses on the history of Ukrainian art of the end of the 11th and beginning of the 20th centuries, as well as preparing a general monographic study on the Ukrainian art postcard.